Deforested tropical landscapes: Unveiling the mechanisms driving tree saplings growth and survival in forest fragments - Leiza A.S.S. Soares; Larissa Rocha-Santos; Deborah Faria; Eduardo Mariano-Neto; Marcelo S. Mielke; José C. Morante-Filho; Maíra Benchimol; Daniela C. Talora; Fernanda A. Gaiotto; Alesandro S. Santos; Júlio Baumgarten; Eliana Cazetta (Global Ecology and Conservation, 2025)
Forest loss poses a critical threat to biodiversity, with species’ ecological traits shaping their sensitivity to anthropogenic disturbances. Forest specialists, such as shade-tolerant plants, are especially vulnerable to local extinction, whereas shade-intolerant species persist more in deforested landscapes. We conducted a field experiment across 39 Atlantic Forest landscapes to assess how forest loss affects sapling growth and survival along a forest cover gradient. We planted and monitored 2496 saplings from four tree species classified as shade-tolerant or shade-intolerant. Using path analysis, we evaluated the direct and indirect effects of landscape (forest cover), local (canopy openness) and sapling variables (leaf mass per area -LMA-, chlorophyll index, herbivory) on sapling performance. For shade-tolerant species, LMA emerged as the main factor influencing height growth, while basal area growth was primarily affected by canopy openness, determined by forest cover. In contrast, for shade-intolerant species, canopy openness—shaped by forest cover—was the dominant driver of both height and basal area growth. However, LMA, chlorophyll content and herbivory also influenced growth. Shade-tolerant species showed nearly double the survival rate of shade-intolerant species, with forest cover being the main driver of mortality for both groups. Our findings underscore the profound impact of forest loss on sapling growth dynamics and the survival of shade-tolerant and intolerant species. Moreover, they highlight a potential decline in forest resilience and the urgent need for restoration actions. Curbing deforestation and implementing restoration programs around existing fragments can be effective strategies to enhance sapling establishment and maximize ecosystem functionality in human-modified landscapes.